Factors Affecting The Readiness of the Dwiwarna High Schools for Industry 4.0 - Firdaus, Rhendy Akhmad; Intani, Yunita Dwi Cahya; Munandar, Aris; Romadhon, Sendi; Pasaribu, Popy Novita (Manager : Jurnal Ilmu Manajemen, 2023)
The process of digital transformation at the education level of Senior High School (SMA) or Vocational High School (SMK) poses a very important challenge on how schools can deal with digital transformation effectively. What factors can affect readiness in facing digital transformation. This study was quantitative based with a research focus on Dwiwarna High School, with the number of respondents in this study was 97 (ninety seven) people consisting of students, educators and education staff, where the method of determining respondents was by purposive sample with a questionnaire and distributed via Google Form. Data processing was carried out using multiple linear regression tests and it was found that the factors of educational program, students, training services and organizations simultaneously influenced the readiness of human resources at Dwiwarna High School towards Industry 4.0. With the addition of the HR readiness variable, the results of the study allow researchers to introduce factors that influence HR readiness for digital transformation as a reference for Dwiwarna High School and also for other educational institutions